On even harmonious labeiings - Youssef, Maged Z. (Utilitas Mathematica, 2019)
In this paper we give a necessary condition for some regular graphs to be even harmonious and we show that the disjoint union of two k-sequential graphs is even 2k-sequential under some conditions and finally we show in some cases that if G is k-sequential then mG is even 2k-sequential for all positive integer m. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.